Hospital Policy in the United Kingdom : Its Development, Its Future - Harrison, Anthony, 1938-; Prentice, Sally (Routledge, 2017)
"Harrison and Prentice aim to provide a source of reference and reflection for those who are concerned with the planning of hospitals themselves or who are concerned with the health care delivery system as a whole. The authors set out a detailed framework for analyzing hospital services in relation to other providers, based on clinical quality, costs of provision, and access. The book also contains a series of recommendations for action."--Provided by publisher.